From Millennium Development Goals to Sustainable Development Goals - Sachs, Jeffrey D (The Lancet (British edition), 2012)
By 2015, most countries will have made meaningful progress towards most of the goals. [...]for more than a decade, the MDGs have remained a focus of global policy debates and national policy planning. Rather than relying on so-called aid voluntarism, in which countries announce their individual aid promises (and then fail to honour them in most cases), countries should agree to transparent and specific standards of financing, such as quotas and assessments (eg, International Monetary Fund quotas and UN dues) related to national incomes, and levies on national greenhouse gas emissions (eg, a few dollars per ton of carbon dioxide emitted per year).